Experiment on morphological and hydraulic adjustments of step‐pool unit to flow increase. Issue 2 (3rd December 2019) - Zhang, Chendi; Xu, Mengzhen; Hassan, Marwan A.; Chartrand, Shawn M.; Wang, Zhaoyin; Ma, Zewei
Abstract: Exceptional flood events with a return period of about 50 years can be destructive to step‐pool channel segments. However, field investigations and flume experiments have not examined the hydraulic and morphological feedbacks of step‐pool morphology during unsteady hydrographs of exceptional flood events. We performed a series of flume experiments with a manually constructed step model, perturbed with three hydrographs that varied in the rate of water supply change. The bed texture, topography, flow regimes, surface flow field and water depth were characterized and measured as the flow rate was increased during the experiments. A distinct pool feature emerged downstream of the manually constructed step when the flow rate exceeded the threshold scaled to the peaks of ordinary flood events in well‐graded mountain streams. The pool feature was modified in several different ways with flow rate increase. The bed surface steadily coarsened, micro‐bedforms developed and became more pronounced, the bed topography became more spatially complex based on analysis using the Hurst exponent, and last, pool depth steadily increased. Pool modification was also linked to the flow regime: the impinging jet regime led to grain size segmentation in the pool while the jump regime contributed to decelerating flow velocity. The steeper rising limb of hydrograph led to a less developed pool feature, with smaller sized micro‐bedforms in the pool bottom to outlet, and higher discharge threshold for distinct coarsening and scouring in the pool. The estimated energy dissipation within the step‐pool unit decreased as a power function from low to high flow, quantified as the ratio h c / H S, where h c is the critical water depth and H S is scour depth. Our results highlight the interaction between morphology, hydraulics, and energy dissipation of step‐pool unit and the crucial role of hydrograph shape on the interaction during flow increase © 2019 John Wiley & Sons, Ltd. Abstract : We performed flume experiments with a manuallyconstructed step model, perturbed with three hydrographs that varied in therate of water supply change. Pool texture, topography, micro‐bedforms, hydraulic regimes and energy dissipation were coupled in time and space as theflow rate increased and the hydrograph changed. The energy dissipation within thestep‐pool unit decreased as a power function from low to high flow conditions.